100 years of nuclear isomers—then and now. (13th February 2020) - Walker, Philip; Podolyák, Zsolt
Abstract: The suggestion that some atomic nuclei would be able to exist in more than one stable or metastable configuration was proposed by Soddy in 1917. Subsequently, the first experimental example of such an isomeric pair was reported by Hahn in 1921, in the form of two metastable states of 234 Pa, then known as UZ and UX2 . Nowadays, of the 3437 nuclides listed in the most recent NUBASE evaluation, 1318 have at least one metastable excited state with a half-life of 100 ns or longer. The present work reviews historical aspects of nuclear isomers, and the different physical mechanisms that lead to their formation. Selected frontiers of contemporary isomer research are discussed, with an emphasis on remote regions of the nuclear landscape. Some possibilities for the electromagnetic manipulation of isomers are included.